Analisis Usability Sistem Informasi Akademik (Studi Kasus SISFO Universitas PGRI Palembang) - Dendi dendi Irawan; dedy syamsuar; tri basuki kurniawan; Muhamad Akbar (Universitas Sriwijaya, 2021)
AbstractThis study aims to determine the level of effectiveness of the usability analysis of the Academic Information System (SISFO) at the PGRI Palembang University. This research uses 2 (two) methods in analyzing, namely, the Webqual 4.0 method and the SUS (System Usability Scale) method. The sample in this research amounted to 385 people both from students, lecturers and staff at the PGRI University of Palembang. The results of this study are, (1) through analysis using Webqual 4.0, it is found that overall usability affects user satisfaction, (2) through analysis using SUS it is found that respondents assess SISFO at PGRI Palembang University. using the system well, after a while of not using it. This research was conducted by applying quantitative methods according to the objective, namely to determine the quality of the academic information system (SISFO) at the PGRI Palembang University. To measure the quality of the academic system, this study uses the Webqual 4.0 method and the System Usability Scale (SUS). Based on the results of this study will be explained as usability. The hypothesis of the utility variable is that the significance value is 0.000 <0.05. From this comparison, the results obtained are H0 rejected and Ha accepted, which means that the usability variable has a significant effect on usability satisfaction (Academic Information System) SUS. keywords: Usability, system Informasi Akademic (Sisfo)